Islamicity performance index dan good corporate governance dalam mempengaruhi kinerja keuangan yang dimoderasi intellectual capital - Rahmawati, Aziza Indah; Rofiuddin, Mohammad (Journal of Management and Digital Business, 2023)
This research analyzes the influence of the Islamicity performance index and good corporate governance on financial performance moderated by intellectual capital. This type of research is quantitative, with a population of Sharia commercial banks registered with the Financial Services Authority for the 2014–2020 period. The number of samples used was 63, and the sampling technique was purposive sampling. The data used is secondary data obtained from the annual report of each Sharia commercial bank, which is then analyzed using the Moderated Regression Analysis (MRA) method. The research results show that the profit-sharing ratio variable does not affect financial performance. While the zakat performance ratio has a negative influence, the board of commissioners and audit committee can positively influence financial performance. Intellectual capital can moderate the influence of the zakat performance ratio, board of commissioners, and audit committee on financial performance. This research can be used as a reference for future researchers regarding financial performance seen from the perspective of the Islamicity performance index and good corporate governance.